Atopic Dermatitis, food allergy and dietary interventions. A tale of controversy - George V. Guibas; Michael Makris; Catherine Chliva; Stamatios Gregoriou; Dimitris Rigopoulos (Sociedade Brasileira de Dermatologia, 2013)
Atopic Dermatitis has long been a controversial entity in regard its relationship to food allergy. Indeed, inter-discipline disparity in the way dermatologists and allergologists perceive the food allergy/atopic dermatitis interplay, hampers the design of concise therapeutic strategies and conveys conflicting messages to the patients. Within this conceptual frame, food exclusion regimes are rendered a contentious option. On the basis of this acknowledgment, we opted to put the emphasis on the discrepant perceptions surrounding such therapeutic regimes and to share our view pertaining to their appropriate implementation.